Coherent mesoscale eddies in the North Atlantic subtropical gyre: 3‐D structure and transport with application to the salinity maximum. Issue 1 (5th January 2017) - Amores, Angel; Melnichenko, Oleg; Maximenko, Nikolai
Abstract: The mean vertical structure and transport properties of mesoscale eddies are investigated in the North Atlantic subtropical gyre by combining historical records of Argo temperature/salinity profiles and satellite sea level anomaly data in the framework of the eddy tracking technique. The study area is characterized by a low eddy kinetic energy and sea surface salinity maximum. Although eddies have a relatively weak signal at surface (amplitudes around 3–7 cm), the eddy composites reveal a clear deep signal that penetrates down to at least 1200 m depth. The analysis also reveals that the vertical structure of the eddy composites is strongly affected by the background stratification. The horizontal patterns of temperature/salinity anomalies can be reconstructed by a linear combination of a monopole, related to the elevation/depression of the isopycnals in the eddy core, and a dipole, associated with the horizontal advection of the background gradient by the eddy rotation. A common feature of all the eddy composites reconstructed is the phase coherence between the eddy temperature/salinity and velocity anomalies in the upper ∼ 300 m layer, resulting in the transient eddy transports of heat and salt. As an application, a box model of the near‐surface layer is used to estimate the role of mesoscale eddies in maintaining a quasi‐steady state distribution of salinity in the North Atlantic subtropical salinity maximum. The results show that mesoscale eddies are able to provide between 4 and 21% of the salt flux out of the area required to compensate for the local excess of evaporation over precipitation. Key Points: 3‐D structure for coherent mesoscale eddies in the North Atlantic subtropical gyre Transient transport of heat and salt Role of mesoscale eddies in shaping the SSS maximum